Antaseden dan Konsekuensi Dari Tourist Satisfaction Wisatawan Curug Tilu Leuwi Opat di Ciwangun Indah Camp - Ilahi, Mareta Herliana Sari Nur; Ernawadi, Yadi (Universitas Batanghari, 2024)
The purpose of this study was to examine the effect of destination image on revisit intention mediated by tourist satisfaction Three Waterfalls of Leuwi Opat at Ciwangun Indah Camp. To achieve this goal, a survey method was used involving 120 respondents who were experienced in visiting tourist destinations that were the object of research. The data collection technique used is cross-sectional studies or one shot study. The instrument has passed the validity and reliability test which includes convergent validity, discriminant validity, and composite reliability. The data analysis technique used is structural equation modeling (SEM) using smartPLS tool version 3.0. From the ten proposed research hypotheses, there are four research hypotheses that are not supported by empirical data. The findings of this study show that unique image affects revisit intention, then affective image affects revisit intention through tourist satisfaction. The results of this study are expected to provide benefits for further research and for managers of objects assessed in the tourism industry that are similar to designing strategies relevant to improving the quality of these attributes.